Monitoring and real-time simulation of power plants: a neural-based environment - Alippi, C.; Cori, A.; Piuri, V.; Pretolani, F. (1996 IEEE Instrumentation and Measurement Technology Conference Proceedings, 1996)
An efficient simulation environment on low-cost computing systems is mandatory to implement advanced control systems, to train the personnel on complex plants, to provide a real-time decision support, and to create a computer-based intelligent automatic system. This allows to improve the competitiveness and the quality of the plant itself and of the operating personnel. In this paper, the use of an advanced environment is presented for the case of power plants, which integrates both conventional equation-based and innovative neural-based models in a single dynamic simulator.